mTOR-inhibitors and post-transplant diabetes mellitus: a link still debated in kidney transplantation - Granata, Simona; Mercuri, Silvia; Troise, Dario; Gesualdo, Loreto; Stallone, Giovanni; Zaza, Gianluigi (Frontiers in Medicine, 2023)
The mammalian target of rapamycin inhibitors (mTOR-Is, Sirolimus, and Everolimus) are immunosuppressive drugs widely employed in kidney transplantation. Their main mechanism of action includes the inhibition of a serine/threonine kinase with a pivotal role in cellular metabolism and in various eukaryotic biological functions (including proteins and lipids synthesis, autophagy, cell survival, cytoskeleton organization, lipogenesis, and gluconeogenesis). Moreover, as well described, the inhibition of the mTOR pathway may also contribute to the development of the post-transplant diabetes mellitus (PTDM), a major clinical complication that may dramatically impact allograft survival (by accelerating the development of the chronic allograft damage) and increase the risk of severe systemic comorbidities. Several factors may contribute to this condition, but the reduction of the beta-cell mass, the impairment of the insulin secretion and resistance, and the induction of glucose intolerance may play a pivotal role. However, although the results of several in vitro and in animal models, the real impact of mTOR-Is on PTDM is still debated and the entire biological machinery is poorly recognized. Therefore, to better elucidate the impact of the mTOR-Is on the risk of PTDM in kidney transplant recipients and to potentially uncover future research topics (particularly for the clinical translational research), we decided to review the available literature evidence regarding this important clinical association. In our opinion, based on the published reports, we cannot draw any conclusion and PTDM remains a challenge. However, also in this case, the administration of the lowest possible dose of mTOR-I should also be recommended.